EFEKTIFITAS INDUKSI LASERPUNKTUR DAN OVAPRIM TERHADAP KECEPATAN PEMIJAHAN DAN JUMLAH TELUR YANG TERBUAHI PADA INDUK LELE (Clarias sp) - Dyah Hariani; Pungky Slamet Wisnu Kusuma (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2016)
This study aimed to test the speed of spawning and the number of fertilized eggs at the parent catfish (Clarias sp) post-induction laserpuncture and ovaprim. This research was conducted at the Laboratory of Biology, University of PGRI Adi Buana Surabaya. The experimental design used was completely randomized design. The study consisted of three treatments, induction laserpuncture in reproductive acupoint precisely at 2/3 of the ventral body for 15 seconds, giving ovaprim 0.4 ml/kg body weight and control (without induction laserpuncture and without giving ovaprim), each repeated six times. Total catfish male parent used as many as 18 heads and parent female catfish as many as 18 heads of all the conditions are ripe gonads. Number of pools that use a total of 18 pools (for spawning catfish). The data collected is spawning catfish speed and the number of fertilized eggs. The results showed that the induction of laserpuncture precisely at 2/3 the ventral body for 15 seconds reproductive acupoint fastest spawning effect and eggs fertilization hight significant than ovaprim and control. Keywords: Induction laserpuncture, ovaprim, eggs fertilization, speed spawning catfish